2019
DOI: 10.1002/brb3.1366
|View full text |Cite
|
Sign up to set email alerts
|

Human entorhinal cortex electrical stimulation evoked short‐latency potentials in the broad neocortical regions: Evidence from cortico‐cortical evoked potential recordings

Abstract: Objective We aimed at clarifying the clinical significance of the responses evoked by human entorhinal cortex (EC) electrical stimulation by means of cortico‐cortical evoked potentials (CCEPs). Methods We enrolled nine patients with medically intractable medial temporal lobe epilepsy who underwent invasive presurgical evaluations with subdural or depth electrodes. Single‐pulse electrical stimulation was delivered to the EC and fusiform gyrus (FG), and their evoked potentials were compared. The correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Article potential between HG and hippocampus, in either direction, was later than the one observed between HG and VLPFC. Our latencies between HG and the hippocampus are in the range of those reported from recording in various temporal lobe sites after entorhinal cortex stimulation (Takeyama et al, 2019). The findings provide support for privileged auditory HG to VLPFC effective connectivity that fundamentally differs from effects in the opposite direction and from those involving the hippocampus.…”
Section: Accesssupporting
confidence: 70%
“…Article potential between HG and hippocampus, in either direction, was later than the one observed between HG and VLPFC. Our latencies between HG and the hippocampus are in the range of those reported from recording in various temporal lobe sites after entorhinal cortex stimulation (Takeyama et al, 2019). The findings provide support for privileged auditory HG to VLPFC effective connectivity that fundamentally differs from effects in the opposite direction and from those involving the hippocampus.…”
Section: Accesssupporting
confidence: 70%
“…To our knowledge, these results have not been described previously in humans. Large or "giant" CCEP responses up to 1 mV in amplitude have been documented in mesial temporal lobe structures in the literature [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Takeyama found that electrical stimulation could induce a unique positive evoked potential, called “widespread P1” (P1w). In the future, this newly evoked potential may provide a new opportunity to evaluate its clinical application as a biomarker of memory disorders in neurological diseases with various memory disorders, such as Alzheimer’s disease (Takeyama et al, 2019 ).…”
Section: Discussion and Futurementioning
confidence: 99%